A new species of Proaphelinoides Girault (Hymenoptera: Aphelinidae) with a key to world species and additional records from Tamil Nadu, India - Menakadevi, C.; Manickavasagam, S. (Zootaxa, 2012)
A new species of Proaphelinoides (Girault) (Hymenoptera: Aphelinidae), P. chidambaramensis Manickavasagam & Me-nakadevi sp. nov., is described from Tamil Nadu, India, and a key to world species is provided. The males of Proapheli-noides are recorded for the first time. Coccophagoides orientalis (Agarwal), Encarsia dorunga Hayat and Eretmocerus rajasthanicus Hayat are also reported as new distributional records for the state of Tamil Nadu, India.